Fear of Missing Out (FoMO) and Impulsive Buying Among Generation Z: An Examination Within the Doom Spending Phenomenon - Pramesty, Jihan Adira; Merida, Sarita Candra (Fathana, 2025)
The rapid development of digital technology has significantly shaped lifestyles and consumer behavior, particularly among Generation Z, who have grown up with social media and e-commerce. One prominent phenomenon within this generation is Fear of Missing Out (FoMO), characterized by anxiety over being left behind in social trends or experiences. On the other hand, the phenomenon of doom spending has emerged, referring to impulsive buying behaviors as a coping mechanism for anxiety about the future. This study aims to examine the relationship between FoMO and impulsive buying among Generation Z in the context of doom spending. Employing a quantitative correlational design, the findings from Pearson correlation analysis revealed a significant positive relationship between FoMO and impulsive buying (r = 0.827, p < 0.05). These results indicate that higher levels of FoMO are associated with a greater tendency toward impulsive purchasing behavior